2006
DOI: 10.1007/s11273-006-9004-8
|View full text |Cite
|
Sign up to set email alerts
|

Dominant environmental factors in wetland plant communities invaded by Phragmites australis in East Harbor, Ohio, USA

Abstract: Elevation, standing crop, disturbance and soil fertility often emerge from studies of freshwater plant communities as the dominant environmental factors determining both species richness and species composition. Few studies in North America have investigated the relationship between these factors and species abundance (standing crop) and species composition in the context of invasion by Phragmites australis. This study explores the influence of key abiotic and biotic variables on species abundance and composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…very little Phragmites prior to treatments, and Phragmites is less successful at establishing under sustained flooding conditions (Armstrong et al 1999;Amsberry et al 2000;Welch et al 2006). However, once established in shallow areas, rhizomes can spread to deeper zones (Cross and Fleming 1989;Amsberry et al 2000), which can explain the presence of Phragmites in deep areas of this study.…”
Section: F-ratios From Ancovas Of Split-plot On Randomized Complete Bmentioning
confidence: 73%
See 1 more Smart Citation
“…very little Phragmites prior to treatments, and Phragmites is less successful at establishing under sustained flooding conditions (Armstrong et al 1999;Amsberry et al 2000;Welch et al 2006). However, once established in shallow areas, rhizomes can spread to deeper zones (Cross and Fleming 1989;Amsberry et al 2000), which can explain the presence of Phragmites in deep areas of this study.…”
Section: F-ratios From Ancovas Of Split-plot On Randomized Complete Bmentioning
confidence: 73%
“…Despite this, promoting native species establishment and richness, through management, is achievable. Welch et al (2006) observed increased diversity with both reduced and increased Phragmites abundance, suggesting that greater species richness can be achieved despite the level of Phragmites dominance, provided that Phragmites does not limit light availability (Haslam 1972;Güsewell and Edwards 1999) or ecologically engineer the site (Minchinton et al 2006). If the goal is to maintain diversity rather than eradicate Phragmites, cutting or cutting and litter removal may be sufficient for a few years following aerial spray and initial CRS treatment.…”
Section: Implications For Species Establishmentmentioning
confidence: 95%
“…ex Steud. (common reed) and Spartina alterniflora Loisel (smooth cordgrass) are two well-known invasive salt marsh species [13], [14] in different regions. Phragmites australis , a salt marsh species native to the east coast of China, is aggressively invading salt marshes along the Atlantic coast of North America [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Chambers et al (1999) detail the spread of Phragmites into tidal wetlands across North America and summarize that disturbance of hydrologic cycles can often promote invasion and reduce biodiversity. Welch et al (2006) found hydrology and topographic factors were driving Phragmites trends in sampled Great Lakes coastal wetlands. In this study, the hydrologic disturbance measure was linked to the magnitude of Phragmites infestation.…”
Section: Resultsmentioning
confidence: 86%